Students’ Perception on Learning English through Songs to Enhance Students' Speaking Ability - Nia Apriani; Eline Rozliya Winarto; Fitri Aprianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2021)
Songs are one of the effective teaching resources to improve students' speaking in English, the use of songs in learning English has many benefits, therefore, this study aims to determine students' perceptions of learning English through songs and to determine student responses to their abilities after learn to speak through songs. This research was conducted in one of the private vocational schools in the city of Cirebon. This research uses qualitative research with case study design. The data source of this research is using questionnaire and interview. To analyze the data, it is done through three stages, namely reduction, data display and verification. Then triangulation of data and sources is used to check the validity of a data. The results of this study illustrate that the use of songs is very effective as a learning resource to improve speaking English through songs. students give a positive perception of learning through songs that have been taught by their teachers in the classroom in the teaching and learning process they are more active and enjoy, become more enthusiastic in learning languages English, by learning through this song makes it easier for them to get more new vocabulary not only that students also know how to pronounce it properly and correctly, learning through this song students can use it in class or even outside class. Keywords: Student perception; student speaking; use of songs